(untitled) (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2023)
It has been two decades since the African Commission on Human and Peoples’ Rights (Commission) rendered its landmark decision in SERAC and CESR v Nigeria. In this landmark judgment, and later in IHRDA and Others v DRC, the Commission explicitly affirmed states’ obligation to investigate, prosecute and redress corporate human right abuses as part of the obligation ‘to adopt legislative or other measures’ under article 1 of the African Charter on Human and Peoples Rights (AfricanCharter). Similarly, states’ obligation to ensure a remedy for corporate human rights abuses is also one of the issues clarified under the ‘Third Pillar’ of the UN Guiding Principles on Business and Human Rights. However, as this obligation is not adequately translated into practice at the national level, corporate human rights abuses committed in Africa continue to be met with impunity and lack of access to effective remedy. Over the last several years, African victims who are denied justice in their domestic jurisdictions have increasingly been turning to home states of corporations to seek remedies. Victims’ access to home state remedies has, however, been significantly restricted in recent years due to various legal barriers, particularly jurisdictional challenges. The article therefore aims to highlight the increasing restriction on African victims’ access to home state remedies and show the need for strengthening domestic remedies in Africa